How the arts can unlocka closed curriculum. (May 2021) - Sikkema, Scott; Lee, Jenny; Spilberg, Joseph; Dahn, Maggie; Yankova, Nickolina; Peppler, Kylie
The COVID-19 pandemic has surfaced educational inequities that pose unprecedented challenges for teaching and learning. Scott Sikkema, Jenny Lee, and Joseph Spilberg of Chicago Arts Partnerships in Education (CAPE) and Maggie Dahn, Nickolina Yankova, and Kylie Peppler of the University of California, Irvine, explain how the arts, which are often relegated to the margins of the curriculum, can help transform disruptions like those brought about by the shift to distance learning into unique opportunities to create more open and equitable learning models. They describe how CAPE's open and inquiry-oriented approach to arts-based pedagogy enabled them to rethink teaching and learning in ways that changed the relationship between teachers and students and gave students more ownership of their learning .